New record of harpacticoid (Copepoda:Harpacticoida) from Tioman Archipelago, Pahang, Peninsular Malaysia - Sham, Azrina; Kassim, Zaleha; Ahmad, Zuhairi; Ahmad Ishak, Nurul Huda; Hasnan, Hazwani Hanim; , (Malaysian Nature Society (MNS), 2019)
Benthic harpacticoid copepod inhabiting corals area of Tioman were investigated. Two species of Laophontidae Scott T, 1904 family and one unknown species of Tetragonicipitidae Lang, 1944 were discovered and described in this paper. Laophonte expansa Fiers, 1986, Quinquelaophonte quinquespinosa Sewell, 1924, and Phyllopodopsyllus Lang, 1944 are the newly recorded from this area. This Phyllopodosyllus sp. is closely related with P. bahamensis Geddes, 1968 and P. hermani Coull, 1969, and P. tenuis Wells & Rao, 1987 but differs from its congeners in: 1) number of setae on Enp-3 of P4; 2) number of setae on Enp-2 of P4; and 3) number of setae on Exp-3 of P4.